Maternal effects on the development of vocal communication in wild chimpanzees - Aisha C. Bründl; Cédric Girard-Buttoz; Tatiana Bortolato; Liran Samuni; Mathilde Grampp; Therese Löhrich; Patrick Tkaczynski; Roman M. Wittig; Catherine Crockford (iScience, 2022)
Summary: Early-life experiences, such as maternal care received, influence adult social integration and survival. We examine what changes to social behavior through ontogeny lead to these lifelong effects, particularly whether early-life maternal environment impacts the development of social communication. Chimpanzees experience prolonged social communication development. Focusing on a central communicative trait, the “pant-hoot” contact call used to solicit social engagement, we collected cross-sectional data on wild chimpanzees (52 immatures and 36 mothers). We assessed early-life socioecological impacts on pant-hoot rates across development, specifically: mothers’ gregariousness, age, pant-hoot rates and dominance rank, maternal loss, and food availability, controlling for current maternal effects. We found that early-life maternal gregariousness correlated positively with offspring pant-hoot rates, while maternal loss led to reduced pant-hoot rates across development. Males had steeper developmental trajectories in pant-hoot rates than females. We demonstrate the impact of maternal effects on developmental trajectories of a rarely investigated social trait, vocal production.